Character Education Program for Student in Islamic Boarding School - Maryati, Mimin; K. Suhandi, Tonny; Permana, Hinggil (KnE Social Sciences, 2020)
This research was conducted to find out Character Education for Students in an Islamic Boarding High School Environment. The study was conducted for 3 months from July to August 2019 in an Islamic boarding school. A qualitative research method is used that aims to examine the condition of natural objects. Data collection techniques were carried out by triangulation, data analysis was inductive and the results emphasize the meaning rather than generalization. The results of this study indicate that the character education policy in boarding high schools stems from the use of the Islamic boarding school label so that all students must be in the same environment. Character education in boarding high schools is carried out in a structured manner and integrated into daily activities, parenting is carried out throughout the day for students from teachers in the school environment and caregivers in the dormitory environment. Evaluation of the conduct of character education is carried out regularly by the boarding trustees and by the school. Keywords: character education, environment, evaluation